Reciprocal Policy Reformulation of Placement of TNI and Polri in Certain Civilian Positions - Karmilla Febbiazka; Eka Deviani; Daffa Ladro Kusworo; Marlia Eka Putri A.T. (KRTHA BHAYANGKARA, 2024)
The State Civil Apparatus (ASN) Law, which was just passed in parliament on October 3, has sparked polemics. This regulation allows the TNI and Polri to fill ASN positions within civil institutions, as outlined in Article 19. ASN positions consist of managerial positions and non-managerial positions. The explanation of the article states that the filling of TNI and Polri positions by ASN and vice versa aims to ensure that ASN, TNI and Polri soldiers have balance and equality in their career development based on the Merit System. This provision in principle contradicts the restriction efforts that have been regulated in the Polri Law and TNI Law. Article 28 Paragraph (3) of the Polri Law explicitly states that Polri members can hold positions outside the police after resigning or retiring from the police service. Article 47 Paragraph (1) of the TNI Law also regulates that soldiers can only hold civilian positions after resigning or retiring from active military service. Thus, the government should reassess and reformulate articles that are counterproductive. In the research conducted by the current author, normative research or doctrinal research and empirical juridical research are used. The main types of data in this research are primary data and secondary data. Data analysis is carried out qualitatively, namely the process of organizing and sorting data into patterns, categories, and one basic description, so that it can be formulated in accordance with the research objectives (substantive theory). This research also conducts comparative theory with other countries' concepts in limiting civilian positions for the TNI and Polri. The urgency of this research is to critically examine the reciprocal policy for the placement of certain civilian positions between TNI soldiers and Polri members with State Civil Apparatus (ASN) employees, which is interpreted as an accelerated expansion of job opportunities, but has implications for the staffing system and civilian militarization in Indonesia in projection.